"Mit sanfter Gewalt": Rape and Sexual Violence in the Works of Christoph Martin Wieland. (8th May 2020) - Speltz, Andrea
Abstract : This article contributes to the historiography of rape and sexual violence in eighteenth‐century German‐speaking Europe. Christoph Martin Wieland (1733–1813) portrays rape and sexual violence in seven literary works from the late 1750s through the mid 1770s. Wieland's texts both attack and affirm contemporaneous legal definitions and social norms governing sexual behavior. The article's main argument is that the theme of rape exposes a tension between Wieland's ideals of gender equality and his practical approach to gender relations. In theory, Wieland acknowledges every human's right to sexual self‐determination, but he nevertheless exploits sexual violence (against males and females) for comic effect, resulting in an unresolved dialectic of the Enlightenment, which underlies his texts